Elementary School Teachers’ Strategies in Overcoming the Challenges of Implementing English Language Learning in Pajo District - Risca Ariska Ramadhan; Desi Rubiyanti (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2025)
This study aimed to analyze (a) the challenges faced by teachers in implementing English teaching at the elementary level, (b) the strategies developed to overcome limitations in competence, resources, and student motivation, and (c) the ways teachers adapt instructional practices to the local context of Pajo District. Employing a descriptive qualitative design, data were collected through in-depth interviews, classroom observations, and documentation, and were analyzed thematically. The findings revealed that teachers encounter multiple obstacles, including limited instructional time, inadequate facilities, and low student motivation. Nevertheless, they developed adaptive strategies such as bilingual instruction, the use of simple and contextualized media, and material adaptation aligned with students’ everyday experiences. These strategies enhanced student engagement, though they did not fully overcome structural constraints. The study highlights the pivotal role of teacher creativity in maintaining English language instruction in resource-constrained settings. It also highlights the necessity of continuous professional training and the provision of adequate learning facilities by schools and government authorities. The implications suggest that locally adaptive pedagogical practices in Pajo can serve as a valuable model for other rural contexts facing similar challenges.